(untitled) (African Multidisciplinary Journal of Research, 2022)
In Kenya, at least 6 listed firms became insolvent and got into liquidation over a period of 10 years (2009 2018) leading to loss of income, unemployment and other negative outcomes. Firm growth has been observed to mediate the relationship between various variables and financial distress of firms though there is little empirical evidence in developing economies particularly for firms that are listed at the Nairobi Securities Exchange in Kenya. The general objective was to investigate the mediating effect of firm growth on the relationship between financial risk and financial distress of firms listed at the Nairobi Securities Exchange, Kenya for the period 2009 2018. This study was based on Wreckers theory of financial di stress, Trade off theory, Distress theory, Early Bankruptcy theory and the Altman’s Z Score Model for financial distress. The study adopted positivism research philosophy and explanatory non experimental and descriptive research designs. The targeted popul ation entailed all 66 firms listed at the Nairobi Securities Exchange, Kenya as at 2018 . Time Series Cross Sectional (Panel) secondary data was analysed . The following diagnostic tests were carried out before delving into data analysis: Tests for Multicoll inearity, Outliers, Heteroscedasticity, Autocorrelation, Linearity, Goodness of Fit, Stationarity and Model Specification. Data analysis was done using descriptive statistics and inferential statistics using Binary Logistic regression model where SPSS vers ion 22 was applied. The findings indicate that Firm growth partially mediates the relationship between financial risk and financial distress of firms listed at the NSE, Kenya at 5% significance levels. The study recommends that financial analysts should come up with recommended firm growth levels that will be optimal in ensuring least financial risk and avoid cases of financial distress of firms. Researchers and institutions should invest in furthering research in areas of factors that mediate the relation ship between financial risk and financial distress . Keywords: Mediating effect, Firm Growth, Financial Risk, Financial Distress, Bankruptcy